Antidepressant Use Among People Prescribed Opioids for Chronic Noncancer Pain. Issue 12 (12th March 2019) - Gisev, Natasa; Nielsen, Suzanne; Campbell, Gabrielle; Santo, Thomas; Mant, Andrea; Bruno, Raimondo; Cohen, Milton; Hall, Wayne D; Larance, Briony; Lintzeris, Nicholas; Farrell, Michael; Degenhardt, Louisa
Abstract: Objective: Although depression and chronic pain often coexist, few studies have examined antidepressant use among people with pain. This study examines the prevalence and characteristics associated with antidepressant use among people prescribed opioids for chronic noncancer pain (CNCP). Design: Baseline data from a prospective cohort study. Setting: Australian community. Subjects: A total of 1166 people prescribed opioids for CNCP. Methods: Baseline data collection consisted of a self-completed seven-day medication diary and telephone interview to collect information on sociodemographic characteristics and mental/physical health using validated questionnaires. Logistic regression was used to examine characteristics associated with antidepressant use, reporting adjusted odds ratios (AORs) and 95% confidence intervals (CIs). Results: Of the 1166 participants, 668 (57.3%) were female, and the median (interquartile range) age was 59 (49–68) years. About half the cohort (N = 637, 54.6%) used antidepressants. Of these, 329 (51.7%) reported moderate to severe depression. Amitriptyline was the most commonly used antidepressant (17.3%). Factors independently associated with antidepressant use were being female (AOR = 1.47, 95% CI = 1.13–1.92), more years lived in pain (AOR = 1.01, 95% CI = 1.00–1.02), and use of nonopioid analgesics (AOR = 1.34, 95% CI = 1.01–1.78), benzodiazepines and related drugs (AOR = 1.84, 95% CI = 1.36–2.49), antiepileptics (AOR = 1.86, 95% CI = 1.38–2.51), and antipsychotics (AOR = 2.15, 95% CI = 1.22–3.77). Conclusions: Antidepressant use is common among people with CNCP prescribed opioids. Those using antidepressants were more likely to use other psychotropic medicines concurrently, highlighting that they are a high-risk population requiring comprehensive assessment to optimize outcomes and reduce potential harms from polypharmacy.